Effectiveness of Generation, Evaluation, and Modification-Cooperative Learning (Gem-Cl) Model Selaras Bakar Batu Cultural Practice in Papua - Budiarti, I. S.; Suparmi, A.; Sarwanto, S.; Harjana, H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study intended to describe the effectiveness of the GEM-CL learning model selaras Bakar Batu cultural practice on chapter heat and temperature. This type of research was quasi-experiment with pretest and post-test control group design. The study population was all students of class XI IPA SMAN 1 Jayapura. The sampling technique used was simple random sampling. The selected classes were XI IPA-3 as an experimental class and class XI IPA-5 as a control class. Data collection instruments were tests based on higher-order thinking skills and questionnaires to collect students’ responses. Data analysis was done by t-test, N-gain, and effect size for data collecting from test data while data from questionnaires were analyzed by descriptive qualitative analysis. It was concluded that the model is effective to apply in physics learning to preserve students’ conceptual understanding and improve students’ higher-order thinking skills. Further study on GEM-CL to other cultural practices and physics chapter in Indonesia would would strengthen this learning model.